Efecto del trasplante temprano en el rendimiento de 4 variedades y 1 línea de arroz con 4 densidades de siembra en el Bajo Mayo – San Martin - Pezo Utia, Ney (2009)
Rice (Oryza sativa) is one of the most important crops in the region San Martin, as a staple food and for being a source of employment. In our region the year 2006 - 2007 have been planted 63,461 hectares and has been obtained that is around 382 144.00 MT of rice in husk (OIA, MINAG, 2007). Who makes the region the second largest producer nationwide, contributing 17% of national production and occupying 40% of the economically active in rural areas (FUDES, 2003) population. Recognizing this production seeks an alternative that better results in performance and quality. To increase yields it requires good agronomic management practices, varieties with disease resistance or otherwise apply sanitary measures according to the reality of ecological zone where rice cultivation. By increasing the performance and quality we seek to generate higher income for the farmer. The introduction of new agricultural management alternatives such as minimum tillage system and Madagascar in the production system of rice cultivation are producing excellent results, with yields ranging up to 20 t / ha. The system consists Madagascar plant a rice plant 10-15 cm before as many roots are formed and consequent suffer less at the time of transplantation. In order to increase productivity, the present research with 4 densities in four varieties and a line of early rice transplanting (15 days after almacigado at the Experimental Station "El Porvenir", October 19 was performed 2004.